2022
DOI: 10.3390/su141610179
|View full text |Cite
|
Sign up to set email alerts
|

UAV-Based High-Rise Buildings Earthwork Monitoring—A Case Study

Abstract: Unmanned aerial vehicle (UAV) is one of the most prominent technologies in the construction industry for data collection purposes. Compared with traditional methods, UAVs collect data faster and more efficiently at a lower cost. One of the construction works that can be monitored using UAV is earthwork. Earthwork monitoring is essential to complete the earthwork on time, according to plan, and within budget. This paper presents an application study on the UAV-based earthwork monitoring of a high-rise building … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 30 publications
0
0
0
Order By: Relevance
“…Based on UAVOP, it is possible to obtain the ground geographic information of the whole tailings pond, so that the storage capacity change data of the tailings pond can be obtained in a more comprehensive and convenient way. Meanwhile, the reliability of the volume measurement based on UAV 3D images has also been confirmed in related research [18,25,27,33,54,55]. In addition, the WebGIS UAV 3D images can be more conveniently and easily shared with users to improve user-friendliness.…”
Section: Analysis Of Storage Capacity Changementioning
confidence: 76%
See 1 more Smart Citation
“…Based on UAVOP, it is possible to obtain the ground geographic information of the whole tailings pond, so that the storage capacity change data of the tailings pond can be obtained in a more comprehensive and convenient way. Meanwhile, the reliability of the volume measurement based on UAV 3D images has also been confirmed in related research [18,25,27,33,54,55]. In addition, the WebGIS UAV 3D images can be more conveniently and easily shared with users to improve user-friendliness.…”
Section: Analysis Of Storage Capacity Changementioning
confidence: 76%
“…Volume measurement based on UAV 3D images typically exhibited a relative erro level within 10% [18,25,27,33,54,55], which indicated that the measurement technique us ing UAV 3D images was sufficiently reliable and could be effectively employed for volum estimation purposes. The WebGIS volume measurement function was utilized on tw phases of 3D images of the tailings pond to measure and analyze the changes in storag capacity during different aerial photography periods, as illustrated in Figure 4.…”
Section: Analysis Methods Of Storage Capacity Changementioning
confidence: 99%